Blood and bile lipid composition and the risk of gallstones at diabetes mellitus of the 1st and 2nd type - V. V. Tsukanov; Yu. L. Tonkikh; A. V. Vasyutin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study lipid composition of blood and bile at diabetes mellitus (DM) of the 1st and 2nd type. Material and methods. Overall 70 patients with the first type DM, 67 patients with the second type DM, 44 patients of the control group #1 and 43 patients of the control group #2 were investigated. All patients underwent diagnostics for the presence of DM and cholelithiasis, blood lipid levels and bloodtoduodenal bile ratio was assessed by biochemical methods. Results. Patients with type II DM and cholelithiasis had total cholesterol level in blood serum 25% higher, triglyceride level - 80% higher and ThomasHofmann index in duodenal bile portion B 20% higher, than patients was gallstone disease and type I DM. Conclusions. Type II DM is followed by more pronounced lipidemia and increase in bile cholesterol saturation, type I DM, but the latter is also associated with lipid metabolism disorders and the risk of gallstone disease development.